2019
DOI: 10.1186/s12881-018-0739-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling gene-environment interactions in longitudinal family studies: a comparison of methods and their application to the association between the IGF pathway and childhood obesity

Abstract: BackgroundThe interactive effect of the IGF pathway genes with the environment may contribute to childhood obesity. Such gene-environment interactions can take on complex forms. Detecting those relationships using longitudinal family studies requires simultaneously accounting for correlations within individuals and families.MethodsWe studied three methods for detecting interaction effects in longitudinal family studies. The twin model and the nonparametric partition-based score test utilized individual outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Through proteomic analysis, Mavreli et al [53] found that PCYOX1, ECM1, HSPG2, CNDP1, and TSP-4 proteins have great potential in the early prediction of gestational diabetes mellitus and can serve as biomarkers for the prenatal screening of the disorder. IGFALS is also a plasma protein synthesized by the liver, and it improves glucose tolerance and insulin resistance by prolonging the half-life and increasing the circulating concentration of insulin-like growth factor-1 [54,55]. These metabolism-related DEPs found in the present study suggest that the occurrence and development of SAP are closely related to metabolic disorders.…”
Section: Discussionsupporting
confidence: 55%
“…Through proteomic analysis, Mavreli et al [53] found that PCYOX1, ECM1, HSPG2, CNDP1, and TSP-4 proteins have great potential in the early prediction of gestational diabetes mellitus and can serve as biomarkers for the prenatal screening of the disorder. IGFALS is also a plasma protein synthesized by the liver, and it improves glucose tolerance and insulin resistance by prolonging the half-life and increasing the circulating concentration of insulin-like growth factor-1 [54,55]. These metabolism-related DEPs found in the present study suggest that the occurrence and development of SAP are closely related to metabolic disorders.…”
Section: Discussionsupporting
confidence: 55%
“…Twin models were adjusted for age and sex. To account for repeated measurements in the twin models, analyses focused on the participants’ grand-averaged values 73 .…”
Section: Methodsmentioning
confidence: 99%